'I don't really understand this BP': Women's knowledge, attitudes, and experiences with preeclampsia in Ghana - Avina Joshi; Titus K. Beyuo; Samuel A. Oppong; Cheryl A. Moyer; Emma R. Lawrence (Public Library of Science (PLoS), 2022)
Preeclampsia and eclampsia are common and serious complications of pregnancies, often presenting as obstetric emergencies. In low- and middle-income countries, limited numbers of healthcare providers and a high volume of critically ill patients can negatively impact provider communication and counseling. Lack of knowledge or awareness of preeclampsia and eclampsia among pregnant women can lead to delays in health seeking behavior. Our study uses grounded theory to explore patients' experience of preeclampsia and eclampsia in a low-resource setting. Participants were postpartum women diagnosed with preeclampsia or eclampsia at Korle Bu Teaching Hospital in Ghana. Interviews consisted of semi-structured, open-ended questions regarding participant understanding of their diagnosis of preeclampsia and eclampsia; counseling from their healthcare providers; and experiences with their delivery, monitoring, and treatment. Qualitative thematic analysis was performed according to the Attride-Sterling analytical framework, using NVivo 12. A total of 45 women were interviewed, 88.9% with preeclampsia and 11.1% with eclampsia. Major themes identified include participants' low general knowledge of their diagnosis, inadequate counseling from healthcare providers, and resulting emotional distress. Women desire more information regarding their diagnosis and associate their health-seeking behaviors with counseling they receive from healthcare providers. Women also acknowledge the systemic barriers that make patient care and counseling challenging for providers, especially in low- and middle-income countries. These findings highlight the need for improved models of counseling and health education for women with pregnancies complicated by preeclampsia and eclampsia.